SURVIVING PRISON: (RE)THINKING THE FEMALE BODY (VERUM: Journal of Scientific Initiation, 2021)
Women, when committing an unlawful act, are doubly penalized: first for the conduct in conflict with the law, and secondly for violating the stereotypical societal ideal of the role of women as mothers, daughters, and wives. Therefore, the aim of this article is to broadly outline the context in which the incarcerated female body exists, and how one might (re)think attitudes that could make them survivors of hardships and a hostile environment. To this end, the proposed methodology is based on a deductive approach and bibliographical research, using books, articles, and journals for data collection. To achieve the goal of this research, the study is divided into parts. Thus, the work aims to define the perception and understanding, initially, of the lives of those deprived of freedom, presenting data and critical reflections on the volume of imprisoned bodies. Subsequently, the focus narrows, directing attention to incarcerated women and their daily struggles faced with the conditions in which their bodies are decomposing. In continuation, the reasons and importance of advancing the debates surrounding the figure of women deprived of liberty are demonstrated, as well as spreading the voices of these women to fight atrocities and promote a system worthy of coexistence. Finally, measures that could transform these women's routines into "life" again will be discussed, namely, public policies, feminism, architectural models, and social issues.
Keywords: Woman; Public Policies; Woes; Feminism